Efek ekstrak daun singkong (Manihot utilissima) terhadap ekspresi COX-2 pada monosit yang dipapar LPS E.coli (The effect of Manihot utilissima extracts on COX-2 expression of monocytes induced by LPS E. coli) - Zahara Meilawaty (Universitas Airlangga, 2013)
Background: Periodontal disease is a common and widespread disease in the community. Gram negative bacteria have a role in periodontitis. These bacteria secrete a variety of products such as endotoxin lipopolysaccharide (LPS), which causes the occurrence of inflammation or infection. The body defense responses are neutrophils and mononuclear cells (monocytes and macrophages). In response to defense mechanism, the body will be expressed enzyme cyclooxygenase (COX) which functions convert arachidonic acid to prostaglandins. Cassava leaf cells known to play a role in reducing inflammation, but the mechanism for inhibiting COX-2, is not known. Purpose: The study was aimed to determine the effect of cassava leaf extract (Manihot utilissima) on expression of enzyme COX- 2 in monocytes which were exposed by LPS E. coli. Methods: This study was in vitro experimental studies with the design of posttest only control group design. The sample was the cassava leaves extract (Manihot utilissima) at concentration of 12.5 % and 25 %. The expression of COX-2 was determined by immunocytochemistry method. Isolated monocytes were incubated in cassava leaf extract, and then exposed to LPS, after washing imunostaning procedure was performed using a monoclonal antibody (MAb) anti-human COX-2. The research data was the number of monocytes that express COX-2. Results: Expression of COX-2 in the group cassava leaf extract was higher than the group that induced by LPS E. coli only. Conclusion: Cassava leaf extract did not inhibit the expression of COX-2 in monocytes which were exposed by LPS E. coli. Latar belakang: Penyakit periodontal merupakan penyakit umum dan tersebar luas di masyarakat. Bakteri yang banyak berperan pada periodontitis adalah Gram negatif. Bakteri ini mengeluarkan berbagai produk antara lain endotoksin lipopolisakarida (LPS) yang menyebabkan inflamasi atau infeksi. Respon pertahanan tubuh pertama adalah netrofil dan sel mononuklear (monosit dan makrofag). Pada respon pertahanan tubuh akan diekspresikan enzim siklooksigenase (COX) yang berfungsi mengubah asam arakidonat menjadi prostaglandin. Daun singkong diketahui berperan dalam menurunkan sel radang, tetapi mekanisme dalam menghambat COX-2, belum diketahui. Tujuan: Penelitian ini bertujuan untuk meneliti ekstrak daun singkong terhadap ekspresi enzim COX-2 pada monosit yang dipapar LPS E. coli. Metode: Penelitian ini merupakan studi eksperimental in vitro dengan rancangan The posttest only control group design. Sampel adalah ekstrak daun singkong (Manihot utilissima) dengan dosis 12,5% dan 25%.